Charging–discharging characteristics of a wound aluminum polymer capacitor. (September 2016) - Jeong, U.H.; Hyung, J.P.; Yoon, Y.G.; Ko, M.J.; Ha, S.G.; Lee, D.H.; Lim, H.W.; Jang, J.S.
Abstract: This study characterized aluminum polymer capacitors, especially when they are charging and discharging. Tests were conducted under various conditions. The following environments were considered: three high-temperature conditions, two high temperature/high humidity conditions, and room temperature. Various operating conditions were also considered, such as charging–discharging, operating, and storage. The test results showed that the capacitance of the wound polymer aluminum capacitor degraded with charging–discharging at low temperature. At lower temperatures, this characteristic accelerated but was mitigated with a dry electrolyte. The degraded capacitances partially recovered when the capacitors were stored at a high temperature. These characteristics were not observed for a conventional liquid aluminum capacitor. This unreported special characteristic of polymer aluminum capacitors should be considered when designing systems such as power electronics. Polymer capacitors are known for their high reliability, especially at high temperatures. At low temperatures, however, the charging–discharging characteristic should be carefully considered. This paper reports on this characteristic of polymer capacitors for consideration by industries. Highlights: A wound polymer capacitor's failure modes presented A wound polymer capacitor's capacitance is degraded at low temperature charging–discharging condition. The degraded capacitances partially recovered at high temperature storage. Degradation was accelerated at lower temperature.